Crianças negras e cotidiano jurídico na Ribeirão Preto do final dos Oitocentos - Ferreira, Emerson Benedito (2019)
Michel Foucault, in his book “The Lives of Infamous Men”, identifies common existences, singular lives, stored in French collections, rescuing from these documents, speeches, conceptions, practices and values of people who only had fragments of their lives recorded by simple fact that they met with power. He made an "anthology of existences". The present work, based on an archaeological methodology and Foucauldian concepts, had the objective of retrieving and mapping fragments of the lives of black children in judicial documents allocated to the Public and Historical Archives of Ribeirão Preto, the Simonense Historical Museum and the Court of Justice of São Paulo between the years 1861 and 1900, and sequentially understand these judicial documents, their speeches and positions, deciphering how the legal machinery worked in its most expressive concept of power-knowledge, and which looks and negotiations the local power launched to administer lives and bodies of those children. The paper also sought to understand if, in that nineteenth century context, "color" and "race" would influence procedural delimitations. We conclude with the work that in the middle of the XIX century a new idea of child was born. This model of child, idealized at that time by the hygienist medicine, would serve only the white, Catholic child of possessions. He would not shelter the black child. It was not just an existing type of racism, but a new type of racism that was born along with the very idea of a child. It was the infancy of this type of racism in Brazil. And this racism would have consequences in court cases involving black children. It would generate selective justice, with judicial decisions affected by race.